Research Progress of the Solid State Lithium-Sulfur Batteries - Wang, HangChao; Cao, Xin; Liu, Wen; Sun, Xiaoming (Frontiers in Energy Research, 2019)
Lithium-sulfur batteries using lithium as the anode and sulfur as the cathode can achieve a theoretical energy density (2,600 Wh.g−1) several times higher than that of Li ion batteries based on the chemical conversion reaction of 6Li + S8 ↔ 8Li2S. The cost effectiveness, together with the intrinsic high energy density of the Li-S batteries, enables it to be an important option for the next generation energy storage devices. However, lithium-sulfur batteries using the liquid electrolyte would lead to the dissolution and “shuttle effect” of polysulfides, which greatly decrease the cycle life and specific capacity. In order to realize long cycle life of the lithium-sulfur battery, it is crucial to address the uncontrolled diffusion of polysulfides. Replacing the liquid electrolyte with the solid electrolyte, which can address the polysulfide dissolution and diffusion problem, inhibit the growth of lithium dendrites on the anode side, and greatly improve the safety and the cycle stability of lithium-sulfur batteries. In spite of the above merits, the performance and application of solid state Li-S batteries are strongly constrained by their low discharge capacity, poor rate performance and unsatisfied cycle life, which need to be overcome by advances in both the materials and the battery design. In this mini-review, the recent research progress of solid-state lithium-sulfur batteries in several aspects, including the sulfur-cathode design, different types of solid electrolyte and Li-S batteries based on them is described/summarized. New insights and synthesis approaches for the stable lithium anode are also summarized. We particularly emphasize the role of the interface in impeding the battery reaction, as well as the construction of the “solid/solid/solid” three-phase reaction boundary. At last, the prospects and challenges in further advancing the scientific understanding and enabling the battery technology viable are presented to shed light on the upcoming research efforts.